THE EFFECT OF FINANCIAL LITERACY AND INCOME ON CONSUMPTIVE BEHAVIOR WITH FINANCIAL BEHAVIOR AS AN INTERVENING VARIABLE ON GAMERS IN PALANGKA RAYA CITY - Febri Oktaviansen Sitmar Anggen Anggen; Solikah Nurwati; Ani Mahrita (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – This researcher aims to determine the effect of financial literacy and income on financial behavior with financial behavior as an intervening variable. Design/Methodology/Approach – This type of research is quantitative. The population of this study is Mobile Legends: Bang-Bang gamers in Palangka Raya City with a sample of 96 respondents using non-probability sampling techniques obtained through questionnaires. Data analysis methods are descriptive analysis and inferential analysis using SmartPLS 4.0 analysis tools. Findings – The results of the study is Financial literacy does not have a significant effect on consumptive behavior on gamers in Palangka Raya City. Income has a significant effect on consumptive behavior on gamers in Palangka Raya City. Financial literacy and income has a significant effect on financial behavior. Financial literacy and income does not affect on consumptive behavior through financial behavior as an intervening variable on gamers in Palangka Raya City. Conclusion and Implications – This study is expected to be a reference for future researchers and further developed, such as looking for other variables that have a possible influence on financial behavior and consumptive behavior.